The Implementation of The Pragmatics Approach to Enhance Speaking Skills in English Language Teaching - Fitria, Yulfa; Rini, Setia (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This classroom action research aimed to improve students’ speaking skills through the implementation of the Pragmatics Approach in English Language Teaching at Class VIII C of MTs SA Pancasila Salatiga. The research was conducted in two cycles during the odd semester of the academic year 2024–2025. Each cycle involved planning, acting, observing, and reflecting. The participants of the study were 23 students of Class VIII C. To determine the effectiveness of the Pragmatics Approach, a pre-test was given before the implementation of the method, followed by post-tests after Cycle I and Cycle II. In addition to observations and interviews, the students' scores from the three tests were analyzed using a paired-sample t-test. The results showed a significant improvement in students’ speaking performance across the cycles. The mean score increased from 65.22 (pre-test) to 70.87 (Cycle I) and then to 77.83 (Cycle II). The t-test analysis confirmed that the improvement was statistically significant. This study concluded that the Pragmatics Approach effectively enhances students’ speaking skills and encourages active and meaningful communication in the classroom..